Alterações funcionais e morfológicas da musculatura esfincteriana em pacientes submetidos a fistulotomia com sedenho cortante - Ana Carolina Parussolo Andre (2018)
Perianal fistula is a frequent condiction that affects young patients. The cutting setton was one of the first operative techniques described for the treatment of perianal fistula, and although it has satisfactory cure rates, functional results are variable in the literature. Objectives: To evaluate the morphology of the anal sphincter muscles using three-dimensional anorectal ultrasound in patients with perianal fistula who underwent fistulotomy with cutting setton. To evaluate the correlations between possible morphological changes identified with anal continence. Methods: Forty patients who underwent surgical treatment for perianal fistula with cutting setton for the treatment of transsphincteric perianal cryptogenic fistula were asked to answer to the Wexner incontinence score and underwent anorectal ultrasonography to assess the anatomical configuration of the anal canal. All anatomical structures of the anal canal and the alterations found were measured and correlated with the clinical complaint of anal incontinence by the Wexner score. Results: The length of total and residual anterior external anal sphincter correlated with a lower incontinence rate (p =0.009 and p = 0.004, respectively). The highest percentage of fibrosis in the anterior external anal sphincter and the largest angle of fibrosis in the internal anal sphincter correlated with higher anal incontinence rate (p = 0.031 and p =0.003 respectively). Conclusion: The treatment with cutting setton causes morphological changes in the anal sphincter that may impact its functionality. Key words: fistula-in-ano, cutting setton, fecal incontinence, Ultrasonography